Physical activity and academic procrastination in Chinese college students: The serial mediating roles of physical self-perceptions and self-esteem - Ren, Kai; Chen, Xing; Zhang, Yanni; Sun, Fang; Peng, Fan (Frontiers in Psychology, 2023)
Studies have demonstrated that physical activity (PA) is negatively associated with academic procrastination. However, there is limited research on the mechanism underlying this relationship. This study aims to explore the relationship between PA and academic procrastination by investigating the roles of physical self-perceptions and self-esteem. 916 college students (650 females; Mean age = 19.11, SD age = 1.04) participated in the study. Participants completed the Physical Activity Rating Scale-3, the Physical Self-Perceptions Profile, the Rosenberg Self-Esteem Scale, and the Academic Procrastination Questionnaires. Descriptive statistics, Pearson’s correlation, and mediating effect analysis were carried out using SPSS 25.0. The results showed that (a) PA, physical self-perceptions, and self-esteem were negatively correlated with academic procrastination, (b) self-esteem mediated the association between PA and academic procrastination, and (c) physical self-perceptions and self-esteem sequentially mediated the association between PA and academic procrastination. These findings have deepened our understanding on the relationship between PA and academic procrastination, highlighting important approaches to deal with academic procrastination.